2021
DOI: 10.1038/s41438-021-00668-y
|View full text |Cite
|
Sign up to set email alerts
|

Strigolactones positively regulate abscisic acid-dependent heat and cold tolerance in tomato

Abstract: Strigolactones are carotenoid-derived phytohormones that impact plant growth and development in diverse ways. However, the roles of strigolactones in the responses to temperature stresses are largely unknown. Here, we demonstrated that strigolactone biosynthesis is induced in tomato (Solanum lycopersicum) by heat and cold stresses. Compromised strigolactone biosynthesis or signaling negatively affected heat and cold tolerance, while application of the synthetic strigolactone analog GR245DS enhanced heat and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 65 publications
1
30
0
Order By: Relevance
“…Apart from their role in drought resistance, the positive role of SLs in the cold and heat stress response is associated with ABA biosynthesis. GR24 5DS application enhanced heat and cold tolerance in tomato, whereas the ABA-deficient mutant compromised the GR24 5DS effects, implying that SL, at least partially in an ABA-dependent manner, allows plants to flexibly acclimate to and overcome these stress conditions ( Chi et al, 2021 ).…”
Section: Crosstalk Between Strigolactones and Other Hormones In Plant...mentioning
confidence: 99%
“…Apart from their role in drought resistance, the positive role of SLs in the cold and heat stress response is associated with ABA biosynthesis. GR24 5DS application enhanced heat and cold tolerance in tomato, whereas the ABA-deficient mutant compromised the GR24 5DS effects, implying that SL, at least partially in an ABA-dependent manner, allows plants to flexibly acclimate to and overcome these stress conditions ( Chi et al, 2021 ).…”
Section: Crosstalk Between Strigolactones and Other Hormones In Plant...mentioning
confidence: 99%
“…To insert the PCR product into the pFGC1008-HA vector behind the cauliflower mosaic virus (CaMV) 35S promoter, the product was digested with Asc I and Kpn I. As described previously, CRISPR/Cas9 vectors were constructed and used to generate bag9 mutants [ 38 ]. Using the CRISPR-P web tool ( (accessed on 11 September 2020)), the target sequences (5′-GCTCGCCGTCGCTATTCCTC-3′) were achieved and subsequently introduced into the Bbs I site of the AtU6-sgRNA-AtUBQ-Cas9 vectors following annealing into the double strands.…”
Section: Methodsmentioning
confidence: 99%
“…SLs bring noticeable changes in plants such as root and shoot architecture patterning [ 7 ], responses to nutrient (N and P) deficiency [ 7 ], and leaf senescence [ 115 ]. Studies showed that cold and heat stress resulted in higher CCD7 and CCD8 gene transcription in tomatoes suggesting that SLs positively regulate tomato heat and cold tolerance responses [ 116 ].…”
Section: Strigolactones and Abiotic Stressmentioning
confidence: 99%
“…The ccd7 mutant in tomatoes showed increased lateral branches, reduced plant height, and higher stomatal conductance than the wild type. However, then the roots of these plants were treated with GR24 under heat stress, and heat-induced wilting was alleviated in both plants [ 116 ]. Heat stress resulted in a decrease in pigment system (PS) II efficiency, quantum yield, and increased REL was overcome in wild type and ccd mutants.…”
Section: Strigolactones and Abiotic Stressmentioning
confidence: 99%